PARTISIPASI DAN AKUNTABILITAS DEWAN PENDIDIKAN PROVINSI DAERAH KHUSUS IBUKOTA JAKARTA DALAM PEMBANGUNAN PENDIDIKAN - Rahmatullah Rahmatullah; Budi Mulyono (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2014)
The existence of the board of education in the province of Jakarta is a form of responsibility and community participation in education. Board of education was positioned as a companion to the government, whose presence is expected to be a strategic partner between the public and the government in the management and organization of education. Duties and functions of the provincial board of education is to provide recommendations to the governor about the the access and quality of education services. As the forum community participation, DKI Jakarta provincial education boards also helped encourage accountability and transparency of the use of public funds with the organizers that the school education department and school committees in open access usage of school funds to the public